KESIAPAN GURU PENDIDIKAN AGAMA ISLAM DALAM PROYEK PENGUATAN PROFIL PELAJAR PANCASILA LEVEL PENDIDIKAN DASAR - Suryani, Irma; Choirunniswah, Choirunniswah; Zulhijra, Zulhijra; Maryamah, Maryamah; Harto, Kasinyo (Universitas Islam Negeri (UIN) Sumatera Utara, 2024)
The research problem is the difficulty teachers face in determining strategies for P5 learning within the Independent Curriculum in elementary schools. Furthermore, the goal of developing a Pancasila student profile that aligns with the objectives of the Ministry of Education, Culture, Research, and Technology's Independent Curriculum has not been achieved. The purpose of this study was to analyze the readiness of Islamic Religious Education teachers in the Pancasila Student Profile Strengthening Project (P5) in elementary schools in Palembang City. This research method was qualitative. The research informants were Islamic Religious Education teachers at SDN 115 Palembang. Data were collected through observation, interviews, and documentation. Data analysis used qualitative analysis. The research results show that elementary school teachers in Palembang City are well-prepared in all aspects. However, ongoing efforts are needed to foster greater enthusiasm and preparedness in the implementation of the Pancasila Student Profile Strengthening Project (P5).